(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Global food security problem has raise concerns on the best agricultural practices that will stand the test of time to replace the already failing conventional agriculture. Yields are reportedly decreasing despite the increasing use of imputes. In the quest of solving this problem, researches have revealed that organic agriculture can get the needed results in a more sustainable manner. Activists of organic agriculture are therefore of the view that it is the best option for food sustainability especially in developing worlds like Africa. Critics also think organic agriculture is a sort of luxurious lifestyle being champion by some few rich consumers at the expense of the vulnerable majority. It is therefore unclear whether organic agriculture is the answer to Africas food crisis. It was shown by literature that organic agriculture is the best model of agriculture for Africa in tackling the food needs of the continent. The superiority of organic agriculture over conventional agriculture was seen in its high yielding crops, high nutrient food produced, less energy consumption and less greenhouse gas produced during production, high drought and flood resistant crops with an overall positive impact on the ecosystem. However, challenges such as lack of national organic agriculture policies, low/no research in organic agriculture, high cost of organic certification and imputes, high illiteracy rate, and under developed markets in most African countries hampers widespread adoption of organic agriculture in Africa. Until these challenges are addressed by governments of African countries, organic agriculture cannot be the answer to Africas food crises.